Knowledge of Olympic Games and attitudes towards Olympic values of student teachers at selected colleges of education in Zambia - Akatama, Mubita (Πανεπιστήμιο Πελοποννήσου, 2016)
The Olympic Games are the acme of sports competition in the world. However, it is often emphasised that they are not just games like any other but go beyond mere celebration. They disseminate values that are aimed at turning young people into responsible citizens of the world. A number of studies have been conducted to determine whether these Olympic values are disseminated by various stakeholders in the Olympic Movement. Many of them have concluded that much more needs to be done. The purpose of this study was to find out the knowledge of Olympic Games and awareness of the Olympic Movement of student teachers at selected colleges of education in Zambia. The study also was to determine the values emphasised by the college curriculum as well as ascertain the values considered important by Physical Education lecturers in these colleges. A total of 155 respondents participated in the study. 141 students were administered questionnaires, 5 were interviewed and 9 lecturers were also interviewed. The study found out that although some students were aware of the Olympic Games and the Olympic Movement, their level of knowledge was low. The study also found out that there were similarities between the values stated in the curriculum as well as those students reported were emphasised by the curriculum, and those held important by Physical Education lecturers. This study can assist stakeholders in Olympic Education such as Zambian educators, OYDC, NOCZ as well as the IOC to exploit the willingness of students to learn more about the Olympic Games, the Olympic Movement and Olympic values. It can also promote acceptance of the values as some of the values are part of the local culture.
Keywords: Olympics; Olympic Values Education Programme; Student teachers - Zambia; Ολυμπιακοί αγώνες; Ολυμπιακές αξίες, Εκπαιδευτικό Πρόγραμμα; Φοιτητές εκπαιδευτικοί - Ζάμπια; Olympic values; Student teachers; Olympic Education; Ολυμπιακές αξίες; Φοιτητές εκπαιδευτικοί; Ολυμπιακή Εκπαίδευση